Rumrunners' paradise [videorecording (DVD)] : Spokane during prohibition - Zimmer, Jim director; Castle, Russ (KSPS, 2012)
New Year's Eve, 1915, was a celebration like no other in Washington State history. This would be the "last call" before prohibition was enacted in Washington, four years before national prohibition. At the stroke of midnight, every saloon in the state would be out of business; and millions of dollars of revenue from the liquor industry would cease to exsist. This is the untold story of a rough-and-tumble era in the life of a raw and still coming-of-age Spokane.